Peningkatan Motivasi Belajar Siswa Melalui Penerapan Ice Breaking Edukatif pada Proses Pembelajaran di Sekolah Dasar Negeri 122358 Sumber Jaya II Pematangsiantar: Penelitian - Sanni Kezia Febriani Hutagaol; Oktri Harlany Situmorang; Lusi Ardina Purba; Gohan Ferdinand Sitinjak; Candi Feronika Situmorang; Helbetty Saragih; Rosmery Finondang; Prini D.E Ambarita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to describe the implementation of ice-breaking in the learning process to increase the learning motivation of fourth-grade students at UPTD SD NEGERI 122358 Sumber Jaya II. This research uses a descriptive-qualitative approach. The sources of this study are teachers and fourth-grade students. The study is motivated by the low learning motivation of fourth-grade students at SD Negeri 122358 Sumber Jaya II in Mathematics subjects. Based on initial observations, the learning process is still dominated by monotonous lecture methods, causing students to feel bored, less focused, and tend to chat during lessons. This study aims to describe the implementation of ice-breaking strategies in increasing students' learning motivation. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that before the implementation of ice-breaking activities, the classroom atmosphere tended to be stiff and unconducive. However, after integrating ice-breaking activities in between lessons, there was a significant change in student behavior. Students became more enthusiastic, cheerful, and refocused on absorbing the lesson material. Ice-breaking was proven to be able to thaw the frozen atmosphere (boredom) and build a more dynamic relationship between teachers and students. The conclusion of this study is that the application of appropriate and varied ice-breaking strategies is effective in increasing students' extrinsic motivation and creating a joyful learning environment in elementary schools.